On Solutions to the Set-Theoretical Yang-Baxter Equation in Wajsberg-Algebras - Tahsin Oner; Tugce Katican (Axioms, 2018)
In this work, we introduce Wajsberg algebras which are equivalent structures to MV-algebras in their implicational version, and then we define new notions and give new solutions to the set-theoretical Yang-Baxter equation by using Wajsberg algebras.